2021
DOI: 10.1002/ls.1569
|View full text |Cite
|
Sign up to set email alerts
|

Water‐based Cu nanofluid as lubricant for steel hot rolling: Experimental investigation and molecular dynamics simulation

Abstract: The lubrication performance of Cu nanofluid was studied through hot rolling tests and non‐equilibrium molecular dynamics simulation. Results showed that nanofluid with 0.5 wt% Cu nanoparticles possessed the optimal effect in reducing the rolling force, finish rolling thickness and rolled surface roughness. The superior lubrication performance was attributed to the formation of protective tribofilm made of Fe/Cu debris, iron and copper oxides as well as amorphous substances with a thickness of about 24 nm, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The application of appropriate lubricants is a convenient and effective approach to solve these issues. With the revolutionary development of nanotechnology in past decades, nanofluids containing nanoparticles in the sized range of 1 ∼ 100 nm have attracted increasing interest in the field of lubrication, such as metal-based nanoparticles (MoS 2 [2], TiO 2 [3], Cu [4]), carbon-based nanoparticles (graphene oxide [5], carbon nanotube [6] and carbon quantum dots [7]) and other inorganic nanoparticles (SiO 2 [8], BN [9]). The application of nanoparticles in fluids can enhance the frictionreduction and anti-wear behavior of lubricants especially under mixed and boundary lubricating conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…The application of appropriate lubricants is a convenient and effective approach to solve these issues. With the revolutionary development of nanotechnology in past decades, nanofluids containing nanoparticles in the sized range of 1 ∼ 100 nm have attracted increasing interest in the field of lubrication, such as metal-based nanoparticles (MoS 2 [2], TiO 2 [3], Cu [4]), carbon-based nanoparticles (graphene oxide [5], carbon nanotube [6] and carbon quantum dots [7]) and other inorganic nanoparticles (SiO 2 [8], BN [9]). The application of nanoparticles in fluids can enhance the frictionreduction and anti-wear behavior of lubricants especially under mixed and boundary lubricating conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional liquid lubricants can effectively reduce friction in many macro-scale metal forming processes. However, they cannot be directly applied in the MDD process because the lubricant film is hard to form and maintain under high contact pressure at the micro scale [ 13 , 14 , 15 , 16 ]. To address this problem, adding nanoparticles (NPs) into the base lubricant has been identified as one of the best solutions [ 9 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they cannot be directly applied in the MDD process because the lubricant film is hard to form and maintain under high contact pressure at the micro scale [ 13 , 14 , 15 , 16 ]. To address this problem, adding nanoparticles (NPs) into the base lubricant has been identified as one of the best solutions [ 9 , 16 , 17 , 18 ]. To further examine the potential of utilising NPs for this purpose, Wu et al [ 19 ] investigated the tribological behaviour of the lubricant with TiO 2 NPs and found that using the nanolubricant can effectively alleviate the overflow and reduce the friction in the steel-to-steel sliding process.…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered that the significant thermal transfer rate was explained by the heat absorption and Brownian motion parameters; and that the effect of entropy, which in the case of Cu-blood flow increased on the walls, was much less significant than these two factors in the flow's centre. Through hot rolling tests and non-equilibrium molecular dynamics simulation, the lubrication capabilities of Cu nanofluid were investigated by He et al [42]. According to the findings, nanofluid containing 0.5 weight per cent of Cu nanoparticles had the best impact on lowering the rolling force, finish rolling thickness, and rolled surface roughness.…”
Section: Introductionmentioning
confidence: 99%